Event‐free survival after radical prostatectomy according to prostate‐specific membrane antigen‐positron emission tomography and European Association of Urology biochemical recurrence risk groups. (12th July 2022) - Roberts, Matthew J.; Chatfield, Mark D.; Hruby, George; Nandurkar, Rohan; Roach, Paul; Watts, Jo Anne; Cusick, Thomas; Kneebone, Andrew; Eade, Thomas; Ho, Bao; Nguyen, Andrew; Tang, Colin; et al.
Abstract: Objective: To assess European Association of Urology (EAU) risk groups for biochemical recurrence (BCR) of prostate cancer relative to prostate‐specific membrane antigen‐positron emission tomography (PSMA‐PET) status and oncological outcomes. Patients and Methods: A retrospective analysis of a study that incorporated PSMA‐PET for men with BCR after radical prostatectomy (RP) was undertaken. EAU risk groups were considered relative to clinical variables, PSMA‐PET findings, and deployment of salvage radiotherapy (SRT). The primary oncological outcome was event‐free survival (EFS) and this was analysed relative to clinical and imaging variables. An 'event' occurred if prostate‐specific antigen (PSA) level rose >0.2 ng/mL above nadir or additional therapies were introduced. Results: A total of 137 patients were included, most of whom had EAU high‐risk disease (76%) and/or low PSA levels (80% <0.5 ng/mL) at the time of PSMA‐PET. EAU risk group was not associated with regional nodal/distant metastasis on PSMA‐PET. Regional nodal/distant metastasis on PSMA PET (compared to negative/local recurrence: hazard ratio [HR] 2.2; P = 0.002) and SRT use (vs no SRT: HR 0.44; P = 0.004) were associated with EFS. EAU high‐risk status was not significantly associated with worse EFS (HR 1.7, P = 0.12) compared to EAU low‐risk status. Among patients who received SRT, both regional/distant metastasis on PSMA‐PET (HR 3.1; P < 0.001) and EAU high‐risk status (HR 2.9; P = 0.04) were independently associated with worse EFS, which was driven by patients in the EAU high‐risk group with regional/distant metastases (38%; HR 3.1, P = 0.001). Conclusions: In patients with post‐RP BCR, PSMA‐PET findings and receipt of SRT predicted EFS. In patients receiving SRT, PSMA status combined with EAU risk grouping was most predictive of EFS. These findings suggest that the EAU risk groups could be improved with the addition of PSMA‐PET.